ChemInform Abstract: Metal‐Free Oxysulfenylation of Alkenes with 1‐(Arylthio)pyrrolidine‐2, 5‐diones and Alcohols. Issue 34 (August 2015) - Yu, Jipan; Gao, Chang; Song, Zhixuan; Yang, Haijun; Fu, Hua
Abstract A wide range of β‐alkoxy sulfides are conveniently and efficiently obtained from alkenes using readily available 1‐(arylthio)pyrrolidine‐2, 5‐diones and alcohols as the oxysulfenylation reagents.